Anti-inflammatory mechanism and active ingredients of the Chinese tallow tree. (25th March 2020) - Fu, Rao; Chen, Fang; Guo, Yiran
Abstract: Ethnopharmacological relevance: The leaf of the Chinese tallow tree (CTT, Sapium sebiferum (L.) Roxb) has been used in Traditional Chinese Medicine (TCM) to treat eczema, shingles, edema, swelling, ascites, scabs, and snakebites. Aim of this study: The present work aimed to explore the antioxidant-related anti-inflammatory mechanisms of CTT leaf and to further investigate their possible active ingredients. Materials and methods: The anti-inflammatory activities of different fractions were determined using a 12- O -tetradecanoylphorbol-13-acetate (TPA) induced model of acute edema in mouse ears. The SOD, CAT and GCL activities and the GSH content of the ear tissue were measured using kits, and the ratio of the treated and control ears was calculated. The anti-inflammatory activities of each single compound and those of a mixture of the compounds were also determined using the TPA-induced model. Results: The anti-inflammatory effects of the three fractions were positively correlated with their increasing GSH capacities. Although the GSH levels decreased during TPA-induced acute edema, the CTT leaf extract could recover these levels by increasing the glutamate cysteine ligase activity. The mixture of ellagic acid, isoquercitrin and astragalin showed an anti-inflammatory effect similar to that of the CTT leaf extract. However, none of these three individual compounds showed comparable activity alone. Conclusion: These results demonstrated that increasing GSH is an antioxidant-related anti-inflammatory mechanism of CTT leaves. In addition, ellagic acid, isoquercitrin and astragalin were found to be jointly responsible for this bioactivity. Graphical abstract: Image 1 Highlights: Fractions with distinct compositions showed different anti-inflammatory activities. Increasing GSH is the antioxidant related anti-inflammatory mechanism. Ellagic acid, isoquercitrin and astragalin all contributed to bioactivity.